Soluble FcγRIIIb (CD16b) and Alpha Defensin as Markers of Neutrophils Activation in Periodontal Disease - Jasim, Fatima Sabah; Al-Ghurabi, Batool Hassan (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
Neutrophils in saliva cause tissue death in inflammatory disorders, including periodontal disease. Identifying biomarkers for neutrophil mediators is crucial for accurate diagnosis in periodontics research. This study is to investigate the salivary levels of soluble cluster of differentiation 16b (sCD16b) and alpha defensin, which are biomarkers of neutrophil activation in patients with periodontal diseases, and to examine the correlation between these levels and clinical periodontal parameters. In this particular case-control study, a total of sixty subjects who were diagnosed with periodontal disease, including 30 with periodontitis and 30 with gingivitis, were recruited. These subjects ranged in age from 17 to 65 years. The study also included 25 healthy volunteers, matching their ages and genders with those of the patients. The periodontal parameters utilized in this study included plaque index, bleeding on probing, probing pocket depth, and clinical attachment loss. We collected saliva samples from all participants, including both patients and controls. In order to estimate the salivary levels of sCD16b and alpha defensin, ELISA was performed. The present findings revealed a significant increase (P≤0.05) in the salivary levels of sCD16b and alpha defensin in periodontitis and gingivitis patients as compared to the control group. Moreover, there was a significant increase (P≤0.05) in the level of sCD16b among periodontitis patients when compared to gingivitis patients, while for the alpha-defensin level, there was no significant difference (P>0.05) between the two groups. On the other hand, this study found a significantly positive correlation for two biomarkers with CAL in the periodontics group. This study indicated that an increase in salivary levels of sCD16b and alpha defensin could be associated with enhanced innate response in periodontics disease, and might serve as biomarkers of neutrophil activation in periodontal disease